Respuesta :
Answer:
k = -2
j = 5
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Algebra I
- Terms/Coefficients
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
Step 1: Define Systems
j + k = 3
j - k = 7
Step 2: Rewrite Systems
j - k = 7
- [Addition Property of Equality] Add k on both sides: j = 7 + k
Step 3: Redefine Systems
j + k = 3
j = 7 + k
Step 4: Solve for k
Substitution
- Substitute in j [1st Equation]: 7 + k + k = 3
- [Addition] Combine like terms: 7 + 2k = 3
- [Subtraction Property of Equality] Subtract 7 on both sides: 2k = -4
- [Division Property of Equality] Divide 2 on both sides: k = -2
Step 5: Solve for k
- Substitute in k [1st Equation]: j - 2 = 3
- [Addition Property of Equality] Add 2 on both sides: j = 5